Անգեղակոթի Ս. Վարդան եկեղեցին հնագիտական հետազոտությունների լույսի ներքո - Ալեքսանյան, Տիգրան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Церковь Св. Вардана в селе Ангехакот традиционно считается одним из святых мест Вардананка. С целью консервации и благоустройства памятника, летом 2018 г. организация «Страна и культура» инициировала комплексные раскопки территории, которые дали очень важные результаты. Статья посвящена основным результатам раскопок, среди которых наиболее важны погребения, выявленные на юго-восточной части церкви. В настоящее время проводятся антропологические и лабораторные исследования скелетов, результаты которых позволят пролить новый свет не только на церковь Ангехакота, но и на изучение памятников, посвященных мученикам Вардананц. St. Vardan Church of Angeghakot village is traditionally considered as one of the shrines devoted to St. Vardan and his companions. In the summer of 2018, the organization “Land and Culture” initiated a complex excavation of the territory in order to preserve and enhance the monument. The excavations yielded very important results. The article is dedicated to the main results of excavations, among which the most important are the burials identified in the southeastern part of the Church. Anthropological and laboratory studies of skeletons are currently underway, the results of which will shed new light not only on the Church of Angehakot, but also on the study of monuments dedicated to the martyrs of St. Vardan and his companions.
Keywords: Christianity; History of the Armenian Church